2020
DOI: 10.1039/d0ra05683a
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization of lutein or beta carotene-loaded cationic liposomes

Abstract: The interactions between carotenoids and membrane constituents are vital for understanding the mechanism of their dynamic action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 65 publications
1
9
0
1
Order By: Relevance
“…35 The range of 3020-2840 cm À1 represents the lipids' characterization and contains the CH bands. [36][37][38][39][40][41] The normalized absorbances (Norm. Abs.)…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…35 The range of 3020-2840 cm À1 represents the lipids' characterization and contains the CH bands. [36][37][38][39][40][41] The normalized absorbances (Norm. Abs.)…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…Xanthan gum-coated liposome has shown high retention ability for encapsulated β-carotene (2 molar β-carotene) during 90 days of storage under refrigerated conditions [ 119 ]. L -α-Dipalmitoylphosphatidylcholine-based liposomes was evaluated for release of β-carotene in simulated digestive system and it was observed that only 5% gum Arabic concentration 10% of total encapsulated β-carotene was released under gastric digestion conditions while 30–40% of total encapsulated β-carotene was released under intestinal digestive fluid [ 315 ]. Liposomes have also been reported improved stability for encapsulated β-carotene [ 117 , 118 , 119 , 120 , 121 , 122 , 123 ].…”
Section: Delivery Systems For β-Carotenementioning
confidence: 99%
“…Xanthan gum coated liposome has shown high retention ability for encapsulated β-carotene (2 molar β-carotene) during 90 days of storage at under refrigerated conditions [228]. L-α-Dipalmitoylphosphatidylcholine based liposomes was evaluated for release of β-carotene in simulated digestive system and it was observed that only 5-10% of total encapsulated β-carotene was released under gastric digestion conditions while 30-40% of total encapsulated β-carotene was released under intestinal digestive fluid [229]. Liposome have also been reported improved stability for encapsulated β-carotene [166,225,228,[230][231][232][233].…”
Section: Liposomesmentioning
confidence: 99%